Pengaruh Sosialisasi Perpajakan, Kesadaran Wajib Pajak, Pemahaman Perpajakan, dan Tarif Pajak Terhadap Kepatuhan Wajib Pajak Pelaku E-Commerce (Studi pada Pelaku Usaha UMKM yang Menggunakan Layanan E-Commerce di Kota Pekanbaru) - Indah Mawaddah; Zirman Zirman; Rezi Abdurrahman (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2023)
This study aims to examine the effect of tax Socialization, understanding of taxation, awareness of taxpayers, and tax rate on the compliance of e-commerce user taxpayers. The object of this study were SMES taxpayers who uses e-commerce service in pekanbaru. This study were using primer data, which distributed all questionnaires directly and online by google form that obtain a sample of 51 respondents. The data obtained were analyzed using the Statistical Package for the Social Sciences (SPSS) data analysis program version 25. The results show that tax socialization and taxpayer awareness affect the compliance of SMES taxpayers who use e-commerce services. Meanwhile, understanding taxation and tax rates have no influence on the compliance of SMES taxpayers who use e-commerce services. Adjusted R2 results of four independent variables silmutantly on the dependent variable had an influence of 34% and the remaining 66% were influenced by other factors not studied in this study.Keywords: tax socialization, understanding of taxation, the awareness of taxpayers, tax rate, taxpayers compliance